Global distributions of calcifying zooplankton abundance and biomass - curated observations (as .CSV) and gridded products (biomass climatologies and model outputs, as NetCDF) - Nielja Knecht; Fabio Benedetti; Urs Hofmann-Elizondo; Nina Bednarsek; Sonia Chaabane; Catharina de Weerd; Katja T C A Peijnenburg; Ralf Schiebel; Meike Vogt (PANGAEA, 2023)
The present datasets are those used and generated by: Knecht et al. (2023). The .csv files contain georeferenced observations of abundances and biomass of shelled pteropods and planktic foraminifera (determined at various taxonomic levels). Two README documents describe the way these were implemented from previous zooplankton data syntheses, ongoing plankton monitoring programs and more recent oceanographic cruises. Two NetCDF (.nc) contain the depth-resolved monthly climatologies of shelled pteropods and foraminifera biomasses. The two other NetCDF contain the global estimates of Mean/Median/Min/Max/Stdev biomass concentrations for shelled pteropods and foraminifera for the surface ocean. These global estimates were obtained through an ensemble of biomass distribution models that is extensively described in Knecht et al. (see preprint cited above). This project has received funding from the European Union extquotesingles Horizon 2020 research and innovation programme under grant agreement no. 862923. This output reflects only the author extquotesingles view, and the European Union cannot be held responsible for any use that may be made of the information contained therein.